MAKNA BAHASA FIGURATIF DALAM LIRIK LAGU “SAKURA” KARYA FARIZ ROESTAM MOENAF - Yerso Kaleka Ana Giri; Karolus Budiman Jama; Narantoputrayadi Makan Malay (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and interpret the meaning of figurative language in the lyrics of the song “Sakura” by Fariz Roestam Moenaf through a stylistic approach. The research method used is descriptive qualitative. Data collection techniques included literature study, critical reading and data integration. Data analysis applied Miles and Huberman's interactive model, which included data reduction, presentation, and conclusion drawing with credibility testing through source triangulation. The results show that the lyrics of “Sakura” utilize six types of figurative language: personification, metaphor, hyperbole, imagery, repetition, and irony. The use of metaphor and personification dominates to transform the abstract concept of love into something more vivid and real. The findings conclude that these lyrics represent inner conflict, deep commitment, and a moral message about the honesty of conscience in order to achieve peace of mind. The figurative language in this song serves as a powerful instrument of emotional communication between the creator and the listener, not merely as an aesthetic embellishment.